2017
DOI: 10.1080/08990220.2017.1292237
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxymethylcytosine (5hmC) and Ten-eleven translocation 1–3 (TET1–3) proteins in the dorsal root ganglia of mouse: Expression and dynamic regulation in neuropathic pain

Abstract: Epigenetic mechanisms are increasingly implicated in chronic pain pathology. In this study, we demonstrate that the novel epigenetic mark 5-hydroxymethylcytosine (5hmC) is present in dorsal root ganglia (DRG) neurons and glia, and its levels increase following nerve injury. Furthermore, we show that the 5hmC-generating Ten-eleven translocation 1–3 (TET1–3) proteins are expressed in a cell-type specific manner in the DRG, with Tet3 displaying differential upregulation after injury, suggesting a potential role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Recent work suggests the involvement of TET1 in pathological pain. TET1 is expressed exclusively in the neurons of the DRG and spinal cord dorsal horn [34,35], 2 major pain-related regions in the nervous system. Peripheral SNL and paw injection of formalin or complete Freund's adjuvant (CFA) increased TET1 expression in ipsilateral spinal cord dorsal horn, but not in the DRG [14,[34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work suggests the involvement of TET1 in pathological pain. TET1 is expressed exclusively in the neurons of the DRG and spinal cord dorsal horn [34,35], 2 major pain-related regions in the nervous system. Peripheral SNL and paw injection of formalin or complete Freund's adjuvant (CFA) increased TET1 expression in ipsilateral spinal cord dorsal horn, but not in the DRG [14,[34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…TET1 is expressed exclusively in the neurons of the DRG and spinal cord dorsal horn [34,35], 2 major pain-related regions in the nervous system. Peripheral SNL and paw injection of formalin or complete Freund's adjuvant (CFA) increased TET1 expression in ipsilateral spinal cord dorsal horn, but not in the DRG [14,[34][35][36][37][38]. Knockdown of spinal TET1 alleviated the formalin-, CFA-, and SNL-induced nociceptive behaviors through blocking TET1-triggered expression of dorsal horn miR-365, Stat3, and BDNF, respectively [35,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The opposite process is DNA demethylation generates 5-hydroxymethylcytosine (5hmC) through the oxidation of 5 mC by TET1-3 [ 35 ]. Literature has shown that TET1-3 is expressed in DRG of both naïve and nerve injury modeling mice [ 36 ]. SNL downregulated the expression of the μ-opioid receptor (MOR) and voltage-gated potassium channel subunit Kv1.2 by increasing their DNA methylation through TET1 in the DRG.…”
Section: Dna/rna Methylation and Chronic Painmentioning
confidence: 99%
“…TET3 was suggested to be the main driving factor for the upregulation of 5hmC in the DRG after nerve injury ( 82 ). Wu et al ( 83 ) further showed that SNL surgery could trigger methylation of Oprml1 and Kcna2 , thereby increasing the amounts of 5mC with a corresponding decrease in the level of 5hmC, thus reducing the corresponding MOR and Kv1.2 protein levels and ultimately causing pain.…”
Section: Dna Demethylationmentioning
confidence: 99%